Lepidium sativum as candidate against excitotoxicity in retinal ganglion cells - Al-Dbass Abeer (De Gruyter, 2021)
Glutamate excitotoxicity is considered one of the major causes of retinal ganglion cell death in many retinal diseases. Retinal ganglion cell degeneration causes severe blindness since visual signals from the eye to the brain are conducted only through retinal ganglion cells. Objective: We aimed to explore the potential ameliorative effects of L. sativum against glutamate excitotoxicity-induced retinal ganglion cell damage. Methods: Pure retinal ganglion cells were divided into a control group (untreated); L. sativum-treated groups in which retinal ganglion cells were treated with 5, 10, 50, or 100 µg/mL L. sativum seed extract for 2 h; glutamate-treated groups in which cells were treated with 5, 10, 50, or 100 µM glutamate for 48 h; and L. sativum/glutamate groups [pretreatment with L. sativum for 2 h (50 or 100 µg/mL) before glutamate treatment at 100 µM for 48 h]. Cell damage was assessed by comet assay and cell viability was by MTT test. Results: Tailed DNA, tail length, and tail moment of the 50 and 100 mM glutamate-treated groups were significantly greater than those of the blank control group, while the L. sativum-treated groups demonstrated nonsignificantly different tailed DNA, tail length, and tail moment compared with the blank control group, but significantly lower values compared with the glutamate-treated groups. Conclusion: L. sativum ameliorated the cell viability in retinal ganglion cells after high-concentration glutamate exposure. L. sativum seed extracts were efficient anti-excitotoxic and antioxidant agent that might improve the clinical presentation of many neurological disorders.